Hydraulic performance of high-velocity channels in flood-prone areas - Hashim, Noor Baharim; Ibrahim, Zulkiflee; Huddleston, David H.; Ng, Boon Chong (Universiti Teknologi Malaysia, 2003)
The presence of disturbances such as bends, contraction, expansion, junction, bridge piers in a drainage system is very common in Malaysia. These hydraulic structures often cause the channel flow to choke and form standing waves. Numerical modelling is a reasonable approach to study these problems. The challenges for this numerical model lie in representing supercritical transition and capturing shocks. For this purpose, an unstructured two-dimensional finite-element model is used to solve the governing shallow water equations. This numerical model utilizes a characteristic based Petrov-Galerkin method implemented with shock-detection mechanism. The model testing demonstrates the ability of this numerical model to reproduce the speed and height of flow with the presence of channel contractions, weir, and bridge pier under different flow conditions. The numerical model results are compared quantitatively with experimental results, published numerical simulation and analytical solution. The model was also applied to Sg Segget and Sg Sepakat channels in evaluating the channels performance. In general, the numerical model satisfactorily computed the water-surface profiles of the experimental data and exact solutions. The results demonstrate that the numerical model provide an alternative tool in validating theoretical finding and determining appropriate designs for flood channels to meet site-specific criteria.